Collisional disruption of highly porous targets in the strength regime: Effects of mixture. (March 2020) - Murakami, Yuichi; Nakamura, Akiko M.; Yokoyama, Koki; Seto, Yusuke; Hasegawa, Sunao
Abstract: Highly porous small bodies are thought to have been ubiquitous in the early solar system. Therefore, it is essential to understand the collision process of highly porous objects when considering the collisional evolution of primitive small bodies in the solar system. To date, impact disruption experiments have been conducted using high-porosity targets made of ice, pumice, gypsum, and glass, and numerical simulations of impact fracture of porous bodies have also been conducted. However, a variety of internal structures of high-porosity bodies are possible. Therefore, laboratory experiments and numerical simulations in the wide parameter space are necessary. In this study, high-porosity targets of sintered hollow glass beads and targets made by mixing perlite with hollow beads were used in a collision disruption experiment to investigate the effects of the mixture on collisional destruction of high-porosity bodies. Among the targets prepared under the same sintering conditions, it was found that the targets with more impurities tend to have lower compressive strength and lower resistance against impact disruption. Further, destruction of the mixture targets required more impact energy density than would have been expected from compressive strength. It is likely that the perlite grains in the target matrix inhibit crack growth through the glass framework. The mass fraction of the largest fragment collapsed to a single function of a scaling parameter of energy density in the strength regime ( Π s ) when assuming ratios of tensile strength to compressive strength based on a relationship obtained for ice-silicate mixtures. However, the dependence on Π s is much larger than that shown for porous targets with different internal microstructures from the targets in this study. The depth of the deep cavity specific to the high-porosity target was well represented by a dimensionless parameter using the compressive strength of both the pure glass and mixture targets. The empirical relationship of cavity depth was shown to hold for various targets used in previous studies irrespective of the internal microstructure of the targets. Highlights: Higher content of impurity made high-porosity sintered target weaker. Impact resistance of high-porosity target depends on the internal microstructure. In contrast, cavity depth is insensitive to the detail of the internal microstructure.